Evaluating survival outcomes and treatment recommendations in resectable gastric cancer - Saad Sabbagh; Iktej Singh Jabbal; María Herrán; Mohamed Mohanna; Sindu Iska; Mira Itani; Barbara Dominguez; Kaylee Sarna; Zeina Nahleh; Arun Nagarajan (Scientific Reports)
Abstract No consensus exists on the optimal therapy for resectable gastric cancer (GC) and gastroesophageal junction (GEJ) tumors, including the effectiveness of chemoradiotherapy versus perioperative chemotherapy (PC). Our study aimed to compare overall survival (OS) outcomes associated with the recommended treatment modalities for GC and GEJ tumors and evaluate treatment trends from 2010 to 2020. A national registry cohort identified patients with ≥ cT2 nonmetastatic GC and GEJ cancer. Treatment modalities were classified as neoadjuvant chemotherapy (NC), neoadjuvant chemoradiotherapy (NCR), PC, adjuvant chemotherapy (AC), and adjuvant chemoradiation (ACR). Kaplan-Meier curve and multivariable Cox regression models evaluated factors associated with OS. A cohort of 7665 patients were included. Patients who received PC had the highest OS (median 86.80 months, 95% CI 73.40-NE), while chemoradiotherapy in the neoadjuvant and adjuvant settings had worse OS than PC and NC (NCR median 47.15 months, 95% CI 44.58–52.27, and ACR median 52.67 months, 95%CI 42.78–63.93). The Cox proportional hazards model showed that NCR and NC had worse survival than PC (HR 1.74, 95% CI 1.50–2.02, p < 0.001 and HR 1.26, 95% CI 1.10–1.44, p = 0.0008, respectively). Additionally, the most utilized modality during 2020 was NC (35.8%), followed by PC (28.0%) and NCR (24.9%). The utilization of PC and NC had the most substantial rise between 2010 and 2020, increasing by 11.0%. The study demonstrates the association of PC with improved OS outcomes for nonmetastatic GC and GEJ tumors. Therapies combining radiation with chemotherapy and extended lymph node dissection correlated with a worse prognosis compared to PC and NC. Despite the association with improved outcomes, national data reveals low utilization rates for PC.